PENERAPAN TEKNIK QUICK ON THE DRAW DALAM PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IXB SMP NEGERI 1 SALO - Dafri, Lena Sesri Dafri Sesri; Yuanita, Putri Yuanita Putri; Solfitri, Titi Solfitri Titi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Â Abstract: This reseacrh based on the students mathematics learning outcomes at grade IXB Junior High School 1 Salo under Minimum Mastery Criteria with a percentage of 4,35% on the subject matter about similarity and then the learning process still teacher center. The research was classroom action research. This research aims to improve learning process and outcomes students of math lesson by implementing Quick on the Draw technic in cooperative learning model tipe STAD at grade IXB Junior High School 1 Salo in the first semester academic years 2014/2015. There are 23 students in the class, consisting 14 boys and 9 girls. The instrument of data collection on this research are observation sheets and mathematics learning outcomes tests. Analysis data of observation was performed with narrative descriptive analysis and analysis data of mathematics learning outcomes was performed with descriptive statistical analysis. From the narrative descriptive analysis showed an improvement of learning process from the prior action to the first cycle and the second cycle. The results of this research showed an increasing number of students learning Mathematic from the basic score with percentage 3,45% to 30,43% on the first test and 56,52% on second test. From the results of this study concluded that Quick on the Draw technic in cooperative learning model tipe STAD can improve learning process and students mathematics learning outcomes at grade IXB Junior High School 1 Salo in the first semester academic years 2014/2015.Key Word : Mathematics Learning Outcome, Cooperative Learning, Quick on the Draw, Class Action Research